Manual de buenas prácticas de manufactura para la empresa Láctea PASTOLAC. - Candelejo Quishpe, Flabio Hernán (2018)
During the development and execution of the research project "Optimization of production in three dairy industries in the province of Cotopaxi from the use of by-products and waste" the training research project "Manual of Good Manufacturing Practices for the production of cheese is developed in the Pastolac Company". An initial characterization of the process under analysis is carried out applying the quality and research methods, the non-application of ISO quality standards was verified, only the documents of four INEN standards appear, which are not applied properly and systematically; deficiencies with the elaboration of innocuous foods, the objective of the present work is the elaboration of a Manual of Good Manufacturing Practices for the production of cheese that contains among other aspects, the policies and objectives of the sanitary quality, organization chart of Good Practices team of Manufacturing, the descriptive flowchart and operating procedures. The study of the elaborated manual, its socialization and subsequent implementation significantly reduce the risk of production with contamination, contributing to the quality of the product. Therefore, this manual becomes a valuable guiding tool for the manager and his workers who produce dairy products and it reports benefits to consumers.